2018
DOI: 10.35870/emt.v2i2.55
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor yang mempengaruhi Kinerja Keuangan Bank Umum Syariah yang terdaftar di Bursa Efek Indonesia (BEI) (Periode 2014-2016)

Abstract: Abstrak. Penelitian ini diharapkan berpengaruh terhadap Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Biaya Operasional Pendapatan Operasional (BOPO) terhadap Return on Asset (ROA) sebagai proksi Kinerja Keuangan perbankan syariah di Indonesia periode 2014- 2016. Populasi dalam penelitian ini adalah 11 bank syariah di Indonesia yang terdaftar di Bursa Efek Indonesia untuk periode tahun 2014-2016, dan sampel diperoleh sebanyak 33 bentuk 11 bank dan 3 periode keuangan repo 2014-2016 dengan purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
2
6
0
5
Order By: Relevance
“…The higher the ratio, the worse the credit quality of banks due to the greater number of bad credit, so that the possibility of bank being in problematic condition is higher and it affects the decline in revenue due to an increase in the cost of productive reserves (Almilia & Herdinigtyas, 2005; Pratiwi, 2012) Therefore, it can be concluded that the ratio of Non Performing Financing (NPF) negatively affects return on assets (ROA). These results are consistent with research conducted by (Adyani, 2011;Fahmy, 2014;Nugroho, 2006;Prastiyaningtyas, 2010;Pratiwi, 2012;Siti Nurkhosidah, 2009;Sulistianingrum, 2013).…”
Section: Npf Influence On Roasupporting
confidence: 91%
See 2 more Smart Citations
“…The higher the ratio, the worse the credit quality of banks due to the greater number of bad credit, so that the possibility of bank being in problematic condition is higher and it affects the decline in revenue due to an increase in the cost of productive reserves (Almilia & Herdinigtyas, 2005; Pratiwi, 2012) Therefore, it can be concluded that the ratio of Non Performing Financing (NPF) negatively affects return on assets (ROA). These results are consistent with research conducted by (Adyani, 2011;Fahmy, 2014;Nugroho, 2006;Prastiyaningtyas, 2010;Pratiwi, 2012;Siti Nurkhosidah, 2009;Sulistianingrum, 2013).…”
Section: Npf Influence On Roasupporting
confidence: 91%
“…The positive effect of Capital Adequacy Ratio (CAR) on Return On Assets (ROA) due to the increase of profitability followed by a decline in the need of reserves establishment in order to anticipate the consequences of increasing risk in line with the optimization of assets productivity, so that the capital adequacy of Islamic Banks as proxy for Capital Adequacy ratio (CAR) increases. The results of the study are consistent with research conducted by (Adyani, 2011;Fahmy, 2014;Prastiyaningtyas, 2010;Rahmi & Anggraini, 2013;Wibowo & Syaichu, 2013;Zulifiah & Susilowibowo, 2014).…”
Section: Car Influence On Roasupporting
confidence: 90%
See 1 more Smart Citation
“…faktor-faktor kinerja juga dipengaruhi oleh motivasi, kepuasan kerja, tingkat stress, kondisi fisik pekerjaan, system kompensasi, desain pekerjaan, komitmen terhadap organisasi dan aspek-aspek ekonomis, serta teknis keprilakuan lainnya (Hamdani et al, 2018).…”
Section: Kinerjaunclassified
“…The banking sector in the life of a country is an agent of development [1,2], because the bank is a financial institution that has a function as a financial intermediary institution [3,4], namely as an institution that collects funds from the public in the form of savings and flows back to the public. in the form of credit or financing [5,6,7].…”
Section: Introductionmentioning
confidence: 99%